Strategi Integrasi Teknologi Pendidikan dalam Pembelajaran Abad 21 (Studi Kasus pada Guru Madrasah Ibtidaiyah di Kabupaten Garut) - Povitasari (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2023)
This research aims to explore the strategies of Madrasah Ibtidaiyah (MI) teachers in integrating educational technology in the context of 21st century learning. The main issue studied was how teachers respond to the demands of the digital curriculum amid limited infrastructure, digital literacy, and Islamic values inherent in school culture. A descriptive qualitative approach was used with a case study method in three MIs in Central Java. Data was collected through semi-structured interviews, participatory observation, and documentation, involving eight MI teachers as purposively selected primary informants. The results of the thematic analysis revealed three main strategies carried out by teachers: (1) technology integration in response to the demands of the Independent Learning curriculum; (2) contextual adaptation to limited facilities, culture, and institutional support; and (3) reflection on spiritual values in the use of learning technology. These findings suggest that the integration of technology by MI teachers is not technocratic but rather reflects a reflective and contextual process that combines pedagogical knowledge, content, and technology (TPACK) with local Islamic values. The implications of this study broaden the understanding of value-based digital pedagogic practices in Islamic basic education, as well as encourage teacher training policies that are contextual, participatory, and transformative. This research also makes a theoretical contribution in adapting the TPACK model in a religious-based education environment. Further studies are recommended to examine similar strategies in 3T areas or madrassas with different social contexts.